A systematic literature review to understand cross-organizational relationship management and collaboration - Diirr, Bruna; Cappelli, Claudia (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2019: Anais do XV Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2019.7820, 2019)
Organizations increasingly need to establish partnerships to face environment changes and remain competitive. This cross-organizational relationship allows organizations to share resources and collaborate to handle business opportunities better. However, besides all benefits, these organizations usually face several challenges during the partnership. This research aims to explore the cross-organizational relationship management, thus outlining the systematic literature review performed to understand the collaboration between different organizations and organizing an ICT related body of knowledge about the topic.